PENGARUH TYPICAL PERSON ENDORSER DALAM IKLAN MINYAK GORENG BIMOLI TERHADAP BRAND IMAGE DAN KEPUTUSAN PEMBELIAN PADA IBU RUMAH TANGGA DI KOTA PEKANBARU - Diana Oktabrillian; Sri Restuti; Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the influence of Typical Person Endorser in Advertisement Cooking Oil Bimoli on Brand Image and Purchase Decision on Housewives in Pekanbaru City. Population in this research is Individual who have seen advertisement of Bimoli cooking oil product which is played by Typical Person Endorser and who have made a purchase. The sampling method was done by using non probability sampling technique so that the number of samples was 130 people. Data analysis technique used is path analysis with help of SPSS program version 18.00. From the test results note that Typical Person Endorser significant effect on Brand Image and Purchase Decision. Brand Image significant effect on Purchase Decision and Typical Person Endorser significant effect on Purchase Decision through Brand Image Bimoli Edible Oil In Pekanbaru City. It is expected that the management of the company to choose the endorser that has the appeal and in accordance with the products offered to increase consumer desire to buy Bimoli cooking oil and trying to convince consumers to buy and consume cooking oil Bimoli with not much consideration.Keywords : Typical Person Endorser, Brand Image and Purchase Decision